2008
DOI: 10.1111/j.1600-0846.2008.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐observer variability in reading of phototest reactions with sharply or diffusely delineated borders

Abstract: It is concluded that if naked-eye readings are to be the outcome measurement, then provocations/protocols producing distinct borders are an advantage. If borders between provoked and unprovoked skin can be expected to be diffuse, i.e. part of a continuum of response, the use of objective, bioengineering techniques such as LDPI is required. Quantitative methods are also the basis for more detailed presentation and interpretation of test results including information on dose response above the minimal erythema d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 17 publications
0
4
1
Order By: Relevance
“…The broad edge in the present study resulted in an estimation of the width of the non-irradiated area, which was less than the expected width based on the provocation set-up. This also appeared at odds with naked eye estimations of width of the reaction in the previous study (7), although this previous study used a test band that was erythematous rather than the present study's non-erythematous band. Apart from using different assessment parameters for the edge characterization, a comparison with the previous study also shows that the choice of algorithm for the estimation of the border width may affect the results.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The broad edge in the present study resulted in an estimation of the width of the non-irradiated area, which was less than the expected width based on the provocation set-up. This also appeared at odds with naked eye estimations of width of the reaction in the previous study (7), although this previous study used a test band that was erythematous rather than the present study's non-erythematous band. Apart from using different assessment parameters for the edge characterization, a comparison with the previous study also shows that the choice of algorithm for the estimation of the border width may affect the results.…”
Section: Discussioncontrasting
confidence: 79%
“…Based on the haemoglobin derivatives quantifying the reactive and the non‐reactive areas, the border width was found to be broader than indicated by the preliminary results of another study (7) using a similar provocation but using the assessment of microvascular perfusion, by laser Doppler perfusion imaging (LDPI), as the assessment parameter. The broad edge in the present study resulted in an estimation of the width of the non‐irradiated area, which was less than the expected width based on the provocation set‐up.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…When performing minimal erythema dose (MED) tests, the clinical evaluation is often based on the degree of erythema according to a 5‐point scale: 0: no erythema; (+): just perceptible erythema; 1+: erythema with a well‐defined border; 2+: erythema with bright redness and induration (skin edema) on palpation; 3+: marked erythema with borders raised above the surrounding skin (skin edema) on palpation. The evaluation of erythema is a subjective assessment, which is subject to both intra‐ and interobserver variation , therefore, several objective measures, like skin color reflectance and skin perfusion with Doppler flowmetry, have been exploited in the MED test evaluation . The subjective visual assessment is, however, still used in the clinical setting.…”
mentioning
confidence: 99%
“…Another limitation of the study is the fact that control reading was performed by one single doctor. This makes it difficult to relate to the possible effects of inter-observer variability that could have affected the results if there were more than one physician performing the control readings, which has in a previous studies shown to be substantial [2,36]. Subsequently, the ultimate setup would be a study with both a somewhat larger subject sample size, and multiple trained observers performing the control readings.…”
Section: Discussionmentioning
confidence: 99%